Characterization and fine mapping of a semi-rolled leaf mutant srl3 in rice - Xiao-qi YU; Wei XIE; He LIU; Wei LIU; Da-li ZENG; Qian QIAN; De-yong REN (Journal of Integrative Agriculture, 2022)
Moderate leaf rolling can maintain leaf erectness, improve light transmittance in the population, and improve light energy utilization, thereby increasing rice yield. This study used ethyl methanesulfonate (EMS) to treat Yunjing 17 (YJ17) and obtained a semi-rolled leaf mutant that was named semi-rolledleaf3 (srl3). We found that the rolled-leaf phenotype was due to the aberrant development of bulliform cells and the loss of sclerenchymatous cells. In addition, the shoot and root length of srl3 seedlings differed from the wild type. The srl3 mutant had significantly lower plant height and seed-setting rate but notably greater tiller number, panicle length, and primary branch number per panicle than the wild type. Genetic analysis showed that a single recessive nuclear gene defined the srl3 mutant, and it was precisely located in a 144-kb region between two insertion-deletion (InDel) markers, M8 and M19, on chromosome 2. In this region, no leaf-rolling-related genes have been reported previously. Thus, the study indicated that SRL3 is a novel leaf-rolling-related gene, and the results laid the foundation for the cloning and functional analysis of the SRL3 gene.